A Y178C rhodopsin mutation causes aggregation and comparatively severe retinal degeneration - Sreelakshmi Vasudevan; Paul S.–H. Park (Cell Death Discovery)
Abstract Rhodopsin is the light-activated G protein-coupled receptor that initiates vision in photoreceptor cells of the retina. Numerous mutations in rhodopsin promote receptor misfolding and aggregation, causing autosomal dominant retinitis pigmentosa, a progressive retinal degenerative disease. The mechanism by which these mutations cause photoreceptor cell death, and the role aggregation plays in this process is still unclear. We recently demonstrated with the P23H and G188R rhodopsin mutants that the severity of aggregation observed in vitro is also reflected in vivo and impacts the rate of retinal degeneration. A Y178C rhodopsin mutant was investigated here to determine if this relationship applies broadly among mutations that cause misfolding and aggregation of the receptor. In vitro characterization indicated the Y178C rhodopsin mutant exhibits similar properties to the more severely aggregating G188R rhodopsin mutant, where the mutant is mislocalized to the endoplasmic reticulum in HEK293 cells and form aggregates that cannot be rescued by treatment with the retinoid 9-cis retinal. Despite these similarities in vitro, the Y178C rhodopsin mutant promoted a more severe retinal degeneration compared to the G188R mutant in vivo in mice. Aggregates of the Y178C rhodopsin mutant labeled by the dye PROTEOSTAT were morphologically similar to those formed by both the P23H and G188R rhodopsin mutants. There was, however, significantly greater photoreceptor cell death occurring independently of PROTEOSTAT-labeled aggregates in mice expressing the Y178C rhodopsin mutant compared to those expressing either the P23H or G188R rhodopsin mutants. Here, we demonstrate that PROTEOSTAT-labeled aggregates are not the sole cause of photoreceptor cell death promoted by the Y178C rhodopsin mutation in vivo, and there may be alternate aggregate forms contributing to cell death in these mice.